The Creation of Self-Proclaimed “Turkic-Tatar Independent Republics” in the Republic of Armenia in the Context of the “Greater Azerbaijan” Program (1918–1919) - Stepanyan, Gevorg (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Looking back at the path taken by the First Republic of Armenia (1918– 1920), which was formed under difficult military and political conditions, it should be noted that this path was unfolded through complex and challenging turns. The Republic lived and operated in complicated internal and external circumstances, where the most urgent issues facing the state required immediate solutions. The independent Armenian state, first and foremost, had to establish its territorial integrity. This commission was also conditioned by the unfavorable attitudes of the newly formed neighboring states (Georgia and Azerbaijan), which had made their aspirations to seize territories historically belonging to Armenia a cornerstone of their state policy.1 It is well known that, having been defeated in the First World War, the Ottoman Empire, following the Armistice of Mudros (October 30, 1918), was forced to withdraw its troops from Transcaucasia, including the occupied territories of Eastern Armenia, and retreat to the borders of 1914.
Keywords: History